PENERAPAN ALGORITMA C4.5 PADA SISTEM INFORMASI KLINIK MATA FITUR REGISTRASI PASIEN - Anang Andrianto, Zakiyah Qurrotul Aini, M. Arief Hidayat (STMIK YADIKA BANGIL, 2015)
Abstract: Eye Clinic located at bangkalan is a clinic tasked with providing eye healt services to the public. One form of service at the eye clinic is the examination of the patient. To performs the examination, patients are required to wait in line according the queue acquired during the registration. At the eye clinic needed a patient registration system that can predict the patient examination time so that the patient was not long time to wait the queue in place. This research is to design and build awebbased system of patients registration using C4.5 algorithm to predict The generated software has been tested can predict the patient examination time so that patients can wait the queue at home. Rule is generated by an algorithm C4.5 accuracy value of 65.8% and 34.2%error rate so that the algorithm can be used in patient registration feature.Keywords: C4.5algorithm, the decision tree, Eye Clinic, Registration Information System